Factors Influencing the Incidence of Anemia in Adolescents in Cinta Damai Village, West Tanjung Jabung in 2024 - Eprina Intami; Septiwiyarsi Septiwiyarsi; Ummu Habibah; Mutianingsih Mutianingsih; Rini Nurdini; Lina Marlina (Lembaga Pengembangan Kinerja Dosen, 2025)
The problem of anemia in adolescents is still a fundamental problem in the world. Anemia is associated with insufficient food intake and low food quality. Factors that correlate with the incidence of anemia in adolescents both in urban and rural areas are age, sex, health status of toddlers (ARI, diarrhea, tuberculosis), physical activity, nutritional status, breakfast, and diet, parenting and so on. This study aims to determine the anemia in adolescents. This study is an observational analytical study with a cross sectional design. This research was conducted in February-March 2024 in Cinta Damai Village, West Tanjung Jabung Regency. The population in this study were all toddlers aged 12-18 years. A sample of 89 people was taken by total sampling technique. Data collection using questionnaire sheets. The data obtained were analyzed univariately, bivariately using chi square and multivariate tests. The results showed that there was a relationship between infectious diseases (p =), toddler diet (p =) and parenting style (p =) with anemia in adolescents because the p value < 0.05. There was no relationship between giving MP-ASI too early and anemia in toddlers with a value of p = 0.647 > 0.05. The results showed that there was a significant relationship between the incidence of anemia during pregnancy with breakfast (p = 0.003), diet (p = 0.001) and head circumference because the p value < 0.05. There is no significant relationship between the incidence of anemia during pregnancy and chest circumference in newborns at the Jambi Kecil Muaro Jambi Health Center in 2023 with p values of 0.001 > 0.05. The most dominant factor affecting anemia in toddlers is the diet of toddlers with a value of p = 0.001 with OR = 13.108. It is hoped that the results of this study can provide information and recommendations to conduct a series of counseling and counseling activities for mothers of toddlers to prevent and overcome the problem of underweight.